Hydrologic modeling with hec-hms :sungai Sarawak Kiri Basin - Adrian, John Ngau (Universiti Malaysia Sarawak, UNIMAS, 2005)
A hydrological simulation model is a rainfall-runoff model that uses rainfall data to stimulate the hydrological processes for an entire watershed on a single event or continuous basis into the outflow hydrograph at the outlet. The Hydrologic Modelling System HEC-HMS is a suitable program for the simulation of rainfall-runoff process.